2005
DOI: 10.1068/b31157
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Making a City More Compact: Neighbours' Interpretation of Urban Infill

Abstract: The quest for more sustainable urban forms has added renewed vigour to urban planning, with various types of urban infill and intensification becoming increasingly popular with local authorities. These approaches seek to achieve environmental and social objectives but, despite the supposed advantages of a more consolidated urban form, infill housing as a strategy for growth management is not always well received by local residents and it remains a contentious issue. In this paper the authors report on an enqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 17 publications
4
55
0
Order By: Relevance
“…Experiences of these projects, however, suggest that while urban infilling had increased activity in the neighborhood, it also decreased feelings of security and traffic safety (Vallance et al, 2005). This is not surprising, because urbanization is among the best predictors of fear of crime (Miceli et al, 2004).…”
Section: Background Neighborhood Safety Planning Strategies In Varioumentioning
confidence: 97%
“…Experiences of these projects, however, suggest that while urban infilling had increased activity in the neighborhood, it also decreased feelings of security and traffic safety (Vallance et al, 2005). This is not surprising, because urbanization is among the best predictors of fear of crime (Miceli et al, 2004).…”
Section: Background Neighborhood Safety Planning Strategies In Varioumentioning
confidence: 97%
“…The interplay of the relationships between policy, place and daily life must be better understood to facilitate the successful introduction of liveability and sustainability policy (Vallance, et al, 2005). This paper presupposes that the physical form of ICHD as space should address all aspects of residents' liveability and sustainability needs including social needs.…”
Section: Resultsmentioning
confidence: 99%
“…Williams (2000) found some evidence of increases in "bad neighbour" effects of noise complaints although causal attribution was difficult to substantiate. Varying tolerance to these different types of Being aware of how noise travels within a building is important for noise management, both from a building design point of view and the residents' perspective of wishing to minimise noise, thereby contributing to greater satisfaction with high density living (Saville Smith, 2010;Vallance, et al, 2005). While it is important to insulate and provide barriers against noise, it is also important to look at measures to control noise at the source.…”
Section: Noise Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Subiaco city in Western Australia, Davison and Rowden (2012) found that residents gave equal significance to the social and experiential meaning of places as they did to physical form and appearances of streets. These subjective aspects of neighbourhood character are regarded as key factors underlying residents' resistance to urban intensification strategies and projects (Davison & Rowden, 2012;Dovey et al, 2009a;Kyttä, Broberg, Tzoulas, & Snabb, 2013;Vallance, Perkins, & Moore, 2005).…”
Section: Neighbourhood Character: Objective Vs Subjective Indicatorsmentioning
confidence: 99%